2010
DOI: 10.1517/14656566.2010.526106
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the treatment of postsurgical pain

Abstract: Pregabalin is a safe and effective medication that may decrease perioperative opioid use in patients with more acute neuropathic pain than acute inflammatory pain. When surgery involves more neuropathic-type acute pain there is growing evidence that pregabalin may decrease the incidence of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 56 publications
(26 reference statements)
0
37
0
1
Order By: Relevance
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9]. Oral pregabalin attenuates pressor response to laryngoscopy and endotracheal intubation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9]. Oral pregabalin attenuates pressor response to laryngoscopy and endotracheal intubation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Durkin et al in their review, had stated that pregabalin is a safe and effective medication that might benefit the surgery involving more neuropathic-type acute pain than acute inflammatory pain, resulting in a decrease in the perioperative opioid consumption [4]. It was also suggested in another recent review that was published when our study was near complete, that pain scores at 24 h following surgery were affected 1 % by the pregabalin dose and 32 % by the surgical type-again lending credence that more neuropathic and painful surgery may allow for a greater pregabalin effect [16].…”
Section: Discussionmentioning
confidence: 99%
“…sparing effects and prevention of chronic postsurgical pain [4]. COX-2 inhibitors are also being studied for their antiinflammatory analgesic effect either alone or in combination with gabapentinoids for postoperative analgesia [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy of oral pregabalin postoperative analgesia and reduction of parenteral analgesics has been demonstrated in several studies. [13,14]. Only few data are published in literature about the cardiovascular effects of pregabalin on the patients undergoing surgery.…”
Section: Name and Address Of Corresponding Authormentioning
confidence: 99%